THE INFLUENCE OF 5-C FACTORS ON RATE OF CREDIT RETURN IN BEEF CATTLE FARMING IN CENTRAL JAVA - Prasetyo, E.; Sunarso, S.; Santosa, P.B.; Rianto, E.; Ekowati, T.; Yuwana, D.M.; Mulyatno, B. (Diponegoro University, 2012)
The aims of study were to analyze (i) income of beef cattle farming, (ii) ability of farmers to meettheir obligation for returning credit, (iii) role of character, capacity, capital, collateral and conditions(5C) and its effect on credit return. The study was conducted using survey methods on farmers (fatteningand cow-calf operation), who use credit. Sample location was determined using two stage clusterrandom sampling based on beef cattle population, namely region of Grobogan, Blora, Rembang,Wonogiri and Boyolali. Number of respondents was 50 for fattening and 50 for cow-calf operation. Datawere analyzed by descriptive and inferential statistic, which consisted of scoring, income and multiplelinear regression. Results showed that income per-year of beef cattle fattening was greater than cow-calfoperation (IDR 8,954,208.00>1,606,786.00), as well as its contribution to the household farmers’income (49.45>14.91%). Credit return ability was 61.35% based on amount of credit IDR 22,482,510.Five-C analysis resulted that character and capacity of farmers were in adequate category, while capital,collateral and condition were IDR 14,932,500.00, IDR 58,740,000.00 and IDR 14,440,600.00. Capitaland collateral had significant effects, while character, capacity and condition had no significant effectson credit return.